2018
DOI: 10.1371/journal.pbio.2005399
|View full text |Cite
|
Sign up to set email alerts
|

The role of inferior frontal junction in controlling the spatially global effect of feature-based attention in human visual areas

Abstract: Feature-based attention has a spatially global effect, i.e., responses to stimuli that share features with an attended stimulus are enhanced not only at the attended location but throughout the visual field. However, how feature-based attention modulates cortical neural responses at unattended locations remains unclear. Here we used functional magnetic resonance imaging (fMRI) to examine this issue as human participants performed motion- (Experiment 1) and color- (Experiment 2) based attention tasks. Results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 88 publications
(157 reference statements)
7
42
2
Order By: Relevance
“…This region has also been described as a hub for visual attention in a study that examined activity in the right posterior middle frontal gyrus in association with a rule-based increase in attention to a particular stimulus (Sebastian et al, 2016). Zhang and colleagues searched for the source of the attentional bias observed throughout the visual processing cortical areas (Zhang et al, 2018). Using dynamic causal modeling of effective connectivity, they were able to conclude that the key hub for the source of the bias lies in the ventral posterior middle frontal gyrus, consistent with the present observation of activity related to the conditional selection of visual stimuli in the ventral posterior middle frontal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…This region has also been described as a hub for visual attention in a study that examined activity in the right posterior middle frontal gyrus in association with a rule-based increase in attention to a particular stimulus (Sebastian et al, 2016). Zhang and colleagues searched for the source of the attentional bias observed throughout the visual processing cortical areas (Zhang et al, 2018). Using dynamic causal modeling of effective connectivity, they were able to conclude that the key hub for the source of the bias lies in the ventral posterior middle frontal gyrus, consistent with the present observation of activity related to the conditional selection of visual stimuli in the ventral posterior middle frontal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired connectivity in the parietal lobe (Kahn et al, ; Peters et al, ) and frontal lobe (van den Heuvel et al, ) have also been described previously. Furthermore, the inferior temporal gyrus, which is known to be involved in visual processes (Papadelis et al, ; Zhang, Mlynaryk, Ahmed, Japee, & Ungerleider, ), has shown significant anatomical connectivity abnormalities in schizophrenia patients (Jeong, Wible, Hashimoto, & Kubicki, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the inferior temporal gyrus, which is known to be involved in visual processes (Papadelis et al, 2016;Zhang, Mlynaryk, Ahmed, Japee, & Ungerleider, 2018), has shown significant anatomical connectivity abnormalities in schizophrenia patients (Jeong, Wible, Hashimoto, & Kubicki, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although one may argue that endogenous attention to different stimulus attributes, including spatial locations, features, and objects, is thought to originate from a common control system known as the dorsal attention network, even within this common framework, attention to a specific attribute is thought to operate within the sensory cortical area that is responsive to the to‐be‐attended stimulus attribute. Furthermore, recent work points to specialized control areas that participate in feature attention but not spatial attention . Exogenous attention is thought to be driven by a different configuration of brain areas .…”
Section: Implicit Minimal Attention—“the Near Absence Of Attention”mentioning
confidence: 99%
“…Furthermore, recent work points to specialized control areas that participate in feature attention but not spatial attention. 69 Exogenous attention is thought to be driven by a different configuration of brain areas. 70 The attentional routing of information through the visual system has been associated with phase synchronization of mutual oscillatory frequencies between adjacent cortical areas, 55 and this may be mediated by subcortical mechanisms.…”
Section: Implicit Minimal Attention-"the Near Absence Of Attention"mentioning
confidence: 99%